2016
DOI: 10.1088/1367-2630/18/5/053032
|View full text |Cite
|
Sign up to set email alerts
|

Current-induced enhancement of DNA bubble creation

Abstract: Current-induced heating of short double-stranded DNA chains is studied within a two-probe transport setup by using the Langevin approach. The electrons are modeled by a tight-binding Hamiltonian. The DNA atomic motion is described by the Peyrard-Bishop-Dauxois atomic potential, coupled with electrons through the Holstein interaction. The solvent environment is accounted for as a classical heat bath. Voltage biases of0.1 0.5 V can effectively break the base pairs and lead to the melting transition, which can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
0
8
0
2
Order By: Relevance
“…Sub-harmonic discrete breathers have been discussed in the driven PBD model, arising from the anti-continuous limit, even for driving frequencies above the linear frequency of the Morse on-site potential where usual breather solutions do not exist [27]. In another context, the spontaneous formation of vibrational hot spots in homogeneous PBD lattices [28] affects macroscopic transport parameters of a charge carrier coupled to DNA structural dynamics [29,30], while, in reverse, electric current is able to form bubbles by exciting the base pairs [31].…”
Section: Introductionmentioning
confidence: 99%
“…Sub-harmonic discrete breathers have been discussed in the driven PBD model, arising from the anti-continuous limit, even for driving frequencies above the linear frequency of the Morse on-site potential where usual breather solutions do not exist [27]. In another context, the spontaneous formation of vibrational hot spots in homogeneous PBD lattices [28] affects macroscopic transport parameters of a charge carrier coupled to DNA structural dynamics [29,30], while, in reverse, electric current is able to form bubbles by exciting the base pairs [31].…”
Section: Introductionmentioning
confidence: 99%
“…DNA is a thread-like chain of nucleotides carrying the genetic information used in the growth, development, functioning and reproduction of all known living organisms and many viruses. During the last decades, neuronal activity and DNA dynamics [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] have received much interest because of their implications in most biological processes governing the behavior of all living cells, animals and plants.…”
Section: Introductionmentioning
confidence: 99%
“…Besides solvent temperature, environmental factors such as salt concentration [42], pH value [43] and external stretching [44] can also influence the local denaturation known as bubble formation in the closed double helix. In [45], authors have demonstrated that voltage bias can excite the base pairs (bp), hence increases the chemical activity of DNA that leads naturally in DNA bubble creation. Interestingly, they have shown that a voltage bias as high as 0.2V is capable of heating the DNA chain up to the melting phase, while for lower biases transient denaturation can occur but can not sustain.…”
Section: Introductionmentioning
confidence: 99%
“…Отметим, что теоретические и экспериментальные исследования различных модификаций ДНК, направленные на изучение свойств транспорта зарядов, развиваются в последнее время очень активно. Изучаются детали механизмов взаимодействия электронов с возмущениями цепочки нуклеотидов [23][24][25], рассчитываются вольт-амперные характеристики молекулы ДНК [26,27], анализируются способы управления характеристиками транспорта зарядов [28,29], исследуется влияние внешней среды [30], рассматриваются как перспективные сложные модификации, включающие ДНК [31][32][33][34][35][36], описываются различные прикладные возможности [37]. В настоящей же работе изучается взаимодействие электрона с мобильным бризером, возбужденным в небольшой группе смежных нуклеотидных пар у одного из закрепленных концов молекулы за счет начальных смещений нуклеотидов или возмущений их скорости.…”
Section: Introductionunclassified